Sodium bicarbonate is safe but not useful in the management of severe diabetic ketoacidosis (Annals of Medical Research, 2023)
Aim: Diabetic ketoacidosis is a cause of high anion gap metabolic acidosis. Sodium bicarbonate treatment is controversial; it should be avoided as much as possible. This study aims to determine the indications of sodium bicarbonate and its effects on the clinical and laboratory findings in diabetic ketoacidosis patients.Materials and Methods: Patients aged between 1 month and 18 years and hospitalized due to diabetic ketoacidosis between 01.01.2018 and 31.12.2022 were included in the study. The patients received sodium bicarbonate in cases of a pH less than 6.9 and/or partial pressure of carbon dioxide less than 15 mmol/L. Length of stay in the pediatric intensive care unit, the recovery time of acidosis, and the insulin infusion duration; respiratory and heart rates, blood gas analyses, and electrolyte levels of the patients in the first two hours of hospitalization were compared between the patients who received sodium bicarbonate and who did not.Results: Forty-four (19%) of 232 patients received sodium bicarbonate. Twenty-five patients received this treatment, although the pH was greater than 6.9, but the pCO2 was less than 15 mm Hg. The length of stay in the PICU, intravenous insulin infusion duration, and acidosis recovery time were significantly higher in the group receiving sodium bicarbonate. Sodium bicarbonate had no significant effect on respiratory and heart rates, pH, partial pressure of carbon dioxide, anion gap, and bicarbonate level. The elevation in the Glasgow coma score was greater in the sodium bicarbonate receiving group.  Neurological deterioration or any other side effects were not detected.Conclusion: Sodium bicarbonate treatment seems to be safe but not useful in the management of diabetic ketoacidosis. However, for determining the indication of this treatment, not only pH, but also partial pressure of carbon dioxide and anion gap should be considered.